(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In this paper I want to show the genesis of a field of discus- sion among human rights organizations and State in rela- tion to the way in which a concept of memory focused on memory sites (former clandestine detention centers, archi- ves, cultural centers) is imposed. I analyse the moments that contributed to enforce the idea that the former secret deten- tion centers should be the core of the institutionalization of memories. To do that, I first briefly examine public policies taken by the new president in 2003, and then I focus on a specific site of memory, Archivo Provincial de la Memoria (Córdoba). I am interested in observing changes and crys- tallizations in order to understand the creating of policies around sites of memory.